2005
DOI: 10.1002/masy.200551149
|View full text |Cite
|
Sign up to set email alerts
|

Solid‐State NMR Characterization of Biodegradable Shape‐Memory Polymer Networks

Abstract: Summary: Copolymer networks synthesized from dilactide and diglycolide were characterized by solid-state 13 C CPMAS NMR in terms of composition, cross-link density, and rate of cross-linking by UV irradiation. The latter is directly evident by a signal at 44 ppm in the 13 C NMR spectrum. Comparison of solid-state NMR data with the determination of the gel content revealed that this NMR method is sensitive to the chemical cross-link density whereas the gel content is also influenced by physical constraints such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…A key requirement for the investigation of hydrolytically degradable SMP is an accurate determination of the SMP network composition 221, 222. The influence of swelling on the mechanical properties of degradable SMP was investigated in urethane networks based on poly[( L ‐lactide)‐ co ‐glycolide] with T trans = T g (Cat.…”
Section: Multifunctionality Of Shape‐memory Polymersmentioning
confidence: 99%
“…A key requirement for the investigation of hydrolytically degradable SMP is an accurate determination of the SMP network composition 221, 222. The influence of swelling on the mechanical properties of degradable SMP was investigated in urethane networks based on poly[( L ‐lactide)‐ co ‐glycolide] with T trans = T g (Cat.…”
Section: Multifunctionality Of Shape‐memory Polymersmentioning
confidence: 99%
“…The polymer networks were also characterized by solidstate 13 C CPMAS NMR in terms of composition, cross link density, and rate of crosslinking as previously reported. 33,34 Comparison of NMR data with the determination of the gel content revealed that the NMR method is sensitive to the chemical crosslink densities whereas the gel content is also influenced by physical constraints such as entanglements.…”
Section: Network Preparation and Characterizationmentioning
confidence: 99%
“…Shape memory polymers have been produced from biodegradable ε-caprolactone (CL) ,,, in physically cross-linked multiblock copolymers incorporating urethanes , or in homopolymers with chain ends modified to chemically cross-link with acrylates or isocyanates in subsequent steps. ,,, High loadings of cross-linking agents are commonly required. Herein, we describe the use of renewable dihydrocarvone to produce 7-methyl-4-(2-methyloxiran-2-yl)oxepan-2-one ( 1 ) on scales sufficient to examine its utility in the preparation of chemically cross-linked statistical copolymers with CL in a facile one-step process.…”
Section: Introductionmentioning
confidence: 99%